Gear Simulation Kit as A Learning Tool - Nuruz Zawanah Abd Aziz; wan muda, wan hanim nadrah (Research and Innovation in Technical and Vocational Education and Training, 2021)
Abstract: Technical students often faced an understanding problem especially in terms of the learning process in theory only. The development of the Gear Simulation Kit as a learning tool is intended to assist educators in basic gear learning. Preliminary studies have found that there is no use and preparation for interactive learning tools where students can explore and experience simulations on their learning topic. Therefore, a study was conducted to design, develop and test the functionality of the Gear Simulation Kit as a Learning Tool. This is to help the educators in varying the delivery method especially for gear topics to students. The Gear Simulation Kit as a Learning Tool was developed using the ADDIE development model. The use of this model is to help researchers in analyzing consumer needs phase, designing the kit, developing kit, experimenting, and engaging theoretically to also perform expert evaluations. Based on the analysis data, it can be concluded that the project was successfully developed and achieved the objectives and research questions. However, some weaknesses need to be improved such as make these kits user-friendly. The development of the Gear Simulation Kit as a Learning tool can help educators in basic gear calculation learning. Keywords: Gear, Simulation Kits, Learning Tools